Hydrogen spillover on Ni-, Pd- and Pt-doped ZnO ultra-thin films: A density functional theory study - Ho Viet Thang (Vietnam Journal of Science, Technology and Engineering, 2025)
Hydrogen spillover plays an important role in heterogeneous catalytic reactions, such as syngas production, hydrogen production, and CO2 conversion. Among metal oxide materials, ZnO films stand out as promising candidates for hydrogen storage, though their pure form has limitations for certain applications. In this study, the hydrogen spillover on Ni, Pd, and Pt-doped ZnO ultra-thin films is investigated by employing the DFT+U method. To this end, the spillover and non-spillover structures of hydrogen are considered, and their electronic structures are evaluated in undoped and doped ZnO ultra-thin films. The calculated results show that the Ni, Pd, and Pt-doped ZnO ultrathin films can alter the electronic properties of the undoped material from insulating to metallic characteristics. While hydrogen spillover cannot occur on undoped ZnO films, it can proceed with 50% coverage of H atoms on Pd-doped ZnO films and 100% hydrogen coverage on Ni- and Pt-doped ZnO films. This study paves the way for synthesising ZnO-based catalysts for hydrogen storage, catalysis, and other desired applications.